Direct Democracy and the Rights of Cultural Minorities in Swiss - Miroslaw Matyja (Polit Journal Scientific Journal of Politics, 2021)
The minorities in Switzerland are in the first place ethno-linguistic minorities, whose are unified by a common language. Therefore, since the foundation of the Confederation in 1848 the Helvetic state has been considered a multilingual country. The confederation and cantons are obliged to protect linguistic minorities. The grounds of the Swiss social structure, with traditional multiculturalism and four national languages are two principles: language freedom (Sprachenfreiheit) and territoriality (Territorialitätsprinzip). Switzerland has no official state religion. Predominant religion is Christianity, the largest religious minorities is established by Islam. The largest Christian denominations are Catholic Church (37.7%) and Swiss Reformed Church (25.5%). The influx of new cultural minorities to Switzerland began after the Second World War and was directly connected with economic migration, with the large influx of gastarbeiters from southern European countries and refugees from the Third World and from the former Yugoslavia.International law includes the protection of national, yet not cultural minorities. In Switzerland the protection of national minorities is also based on international standards. Is the Swiss multiculturalism an example for other countries?